Nomenclatural novelties in Cheiridopsis (Ruschieae: Aizoaceae) - Powell, Robyn F.; Boatwright, James S.; Klak, Cornelia; Magee, Anthony R. (Phytotaxa, 2018)
The recent study by Powell et al. (2017) showed that the species previously included in the genera Odontophorus N.E.Brown (1927: 12) and Ihlenfeldtia H.E.K.Hartmann (1992: 47) should be recognized under the Southern African endemic genus Cheiridopsis N.E.Brown (1925: 412) (Ruschieae Schwant. ex Ihlenf., Schwant. & Straka, Aizoaceae Martinov). In the new circumscription of Powell et al. (2017), Cheiridopsis comprises of 38 species which belong to three subgenera, i.e. subgen. Cheiridopsis N.E.Brown (1925: 412), subgen. Aequifoliae (1983: 59), and subgen. Odontophoroides H.E.K.Hartmann (1983: 59) (see Hartmann & Dehn 1987, Powell et al. 2017).